Global, regional and national trends in the burden of persistent pulmonary hypertension of the newborn and essentials of its management from 1993 to 2023: a scoping review - Huang, Yan; Yang, Ting; Liang, Xiaoqin; Chen, You; Zhou, Ping; Yu, Zhangbin; Zhong, Guichao; Zhang, Lian (Frontiers in Pediatrics, 2025)
BackgroundPersistent pulmonary hypertension of the newborn (PPHN) is a frequent neonatal emergency in the neonatal intensive care unit (NICU), representing a challenging condition that has not been extensively studied. PPHNremains associated with a high mortality and morbidity.ObjectiveThis scoping review was undertaken to provide a global overview of several key aspects: (1) the prevalence/incidence and etiologies of PPHN, (2) the mortality rate linked to PPHN during hospitalization and the primary causes of such mortality, (3) the risk factors related to PPHN, and (4) the approaches to managing PPHN. The aim of this scoping review was not to assess the methodological soundness of the identified studies, but instead to deliver a broad, comprehensive perspective on PPHN, identify gaps within the current literature, and outline potential avenues for future research. The results are anticipated to assist in developing public health strategies aimed at reducing the morbidity and mortality tied to PPHN globally.MethodsWe conducted a digital search in MEDLINE and the Cochrane Library, from January 1, 1993 to December 31, 2023.We incorporated observational studies, interventional studies, and reviews that provided adequate data on the incidence/prevalence, mortality rates, predictors, etiological factors, diagnosis, and management of PPHN among the general neonatal population (age 0–28 days old). This procedure followed the guidelines set by the Preferred Reporting Items for Systematic Reviews and Meta-Analysis Extensions for Scoping Reviews (PRISMA-ScR). Additionally, we utilized the methodological framework for scoping reviews as outlined by Arksey and O'Malley, which consists of formulating the research question, conducting a search for pertinent studies, selecting the studies, organizing the data, and compiling, summarizing and reporting the findings.ResultsA total of 128 research articles were collected from 27 countries categorized as either high-income or low- and middle-income countries (LMICs). The prevalence of PPHN ranges from 0.1%–8.1% in the different study populations. The highest global prevalence rates are observed in Europe and Asia, while lower prevalence rates are reported in the Americas and Africa. Neonatal infections are the leading cause of PPHN in Asia and the Americas, whereas meconium aspiration syndrome predominates in Europe. Several independent risk factors for PPHN include premature birth, male sex, ethnicity, extremes of birth weight, advanced maternal age, maternal obesity, multiple births, maternal smoking, pregestational/gestational diabetes mellitus, infectious history, caesarean delivery, antenatal drug exposure, fetal distress, APGAR score and meconium-stained amniotic fluid. The PPHN-related in-hospital mortality rate associated with PPHN ranges from 3.0%–57.9%, with the highest rates reported in Asia and the lowest in the United States of America (USA) and the United Kingdom (UK). It is advised that clinical evaluation incorporates the oxygenation index (OI) to assist in guiding medical practice.ConclusionPPHN has a high global burden, driven by neonatal infections and meconium aspiration syndrome, particularly pronounced in LIMCs where there is a pressing need for more intensive treatments and innovative solutions, ideally supported by region-specific subsidies, to address this concerning burden.